Adverse events of radioimmunotherapy for non-Hodgkin lymphoma: A systematic review and meta-analysis. (September 2021) - Sharda, Esha; Patel, Raahil S.; Juárez-Salcedo, Luis Miguel; Dalia, Samir; Hanna, Catherine H.; Gruhonjic, Hanan; Ponnaganti, Bharat S.; Mhaskar, Rahul
Highlights: Radioimmunotherapy combines monoclonal antibodies for a specific malignant cell target and radiation for the destruction of these cells. RIT represent a safe and effective therapeutic option for patients with lymphomas, both in maintenance and relapsed/refractory settings. It is thought that there is an association of RIT and second neoplasms (AML or MSD), but is not clear. With the results of this meta-anaylsis we conclude that RIT has no increased risk of MDS or secondary cancers in patients who receive it. Abstract: Non-Hodgkin's lymphoma continues to be a highly prevalent entity in the general population. Currently, there are multiple treatment schemes based on chemotherapeutic agents with a great success rate. However, there is a non-negligible percentage of patients who may relapse or be refractory. In this sense, new therapeutic options have emerged in the search for adequate responses, such as monoclonal antibodies that target the CD20 molecule. Another valid option is radioimmunotherapy (RIT), which combines using monoclonal antibodies for the specific targeting of malignant cells and radiation to destroy these cells. Despite the promising results that favor RIT in several clinical studies in different target populations and types of NHL, one situation to consider is the association of this therapy and second neoplasms (acute myeloid leukemia (AML) or myelodysplastic syndrome (MSD)). In this sense, we have proposed this meta-analysis to analyze the published information and determine the incidence of this association and determine this therapy's safety.